2013
DOI: 10.3109/08923973.2013.803572
|View full text |Cite
|
Sign up to set email alerts
|

Biologically relevant doses of mixed aflatoxins B and G up-regulate MyD88, TLR2, TLR4 and CD14 transcripts in human PBMCs

Abstract: Immunotoxicity of AFs on PBMCs may be mediated by up-regulation of key immune-surveillance molecule transcripts. The description of these effects induced by AFs on PBMCs are novel and should be taken into account when considering AF-related infectious and noninfectious diseases in areas highly exposed to AFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…Hence, we aimed to evaluate the neuroimmunotoxic effects of low concentrations of the well-known and potent toxin at the cellular and molecular level in different tissues. We have shown active metabolism of the low level of aflatoxins and its immune dysregulatory effects on different types of human leucocytes [8, 21, 27]. We have also recently shown that murine microglial cells can be activated to produce free radicals and initiate inflammatory responses upon exposure to a low quantity of AFB 1 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we aimed to evaluate the neuroimmunotoxic effects of low concentrations of the well-known and potent toxin at the cellular and molecular level in different tissues. We have shown active metabolism of the low level of aflatoxins and its immune dysregulatory effects on different types of human leucocytes [8, 21, 27]. We have also recently shown that murine microglial cells can be activated to produce free radicals and initiate inflammatory responses upon exposure to a low quantity of AFB 1 [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AF dysregulate neutrophil functions in a bovine model, resulting in a decreased phagocytosis and intracellular ROS production (Mehrzad et al, 2011). Further, pathogen recognition is impaired in human leukocytes by AF treatment (Malvandi et al, 2013). Exposure of pigs to AF-contaminated feed increases their susceptibility to infection and reduces vaccine-induced protection, mainly through the dysregulation of T-cell polarization (Meissonnier et al, 2008;Venturini et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Splenic immune cells and brain (sagittal sections of frontal part of whole brain) were separated accordingly [10,16]. The harvested RBC-free splenic cell suspensions were then washed (400 × g, 10 min, 4°C) twice with RPMI-1640, counted (in nigrosin solution) in a Neubauer chamber, and after cell viability assessment using nigrosin solution and the Neubauer chamber, in which necrotic cells appeared bright and dark-blue in the mixture [10][11][12][13][14][15][16], respectively, the cells and brain were eventually used for further cellular and molecular analyses.…”
Section: Mice and Experimental Proceduresmentioning
confidence: 99%
“…TLR are also involved in many neurodegenerative diseases [3,[6][7][8]. TLR have also been increasingly used as novel immunemolecules to extrapolate dysregulatory/toxicity of hazard materials [9][10][11][12][13]. Studies on the effects of acute restraint stress (ARS) on TLR are rare.…”
Section: Introductionmentioning
confidence: 98%